From Pacing to Rapport: Building Communication with Generation Z in Smart City Laboratory - Suprijandoko, Firman (Monas: Jurnal Inovasi Aparatur, 2024)
This research is part of a series of studies under the broad theme of "Smart-Pusdiklat'' within the National Cyber and Crypto Agency (BSSN). The research question addressed is how instructors use the Pacing Phase to Rapport to build communication in the learning process in the Smart City Laboratory. The study revealed that training participants, predominantly from Generation Z, faced challenges such as boredom, loss of focus, and difficulty making choices. Meanwhile, instructors involved were from Generation X and Y. The research highlights key considerations for instructors to ensure effective communication in the classroom. What aspects should instructors pay attention to in order to ensure effective and flawless communication in the classroom? This study employs an exploratory research method with a qualitative approach, aimed at exploring a new phenomenon that has not been previously researched. This is a novelty in the context of the Smart City Laboratory implementation. There are 4 (four) important aspects of the Pacing Phase that must be done to achieve Rapport: Active listening and engagement, Pacing Body Language and Breathing, Technology Integration, Connecting Learning Objectives to Real Life, and Short and Engaging Content, which aligns with the preferences and learning styles of generation Z.